Encapsulamento do agente de biocontrole Trichoderma sp. em um sistema de nanocelulose bacteriana para a proteção e liberação em aplicações na agricultura - Gudoski, Ramicieli (2025)
The increasing global demand for food has driven the search for sustainable agricultural practices that maximize crop productivity while minimizing environmental impacts. Among the promising strategies, the use of biocontrol agents such as Trichoderma sp. stands out for its effectiveness in promoting plant growth and suppressing phytopathogens. However, the low stability and short shelf life of microbial inoculants limit their large-scale application. To overcome this challenge, this study developed an encapsulation system for Trichoderma sp. using bacterial nanocellulose (BNC), with the aim of improving its protection, viability, and controlled release in the field. The methodology involved the production of BNC, followed by the preparation of an oxidized suspension mediated by the TEMPO reagent. Three formulations were prepared using a 1% (w/w) oxidized BNC suspension combined with carboxymethylcellulose (CMC), alginate, and xanthan gum (XG). The first formulation consisted of BNC 1% (w/w), CMC (2%), and XG (0.2%); the second of BNC 1% (w/w), CMC (1%), and alginate (1%); and the third of BNC 1% (w/w), CMC (2%), and alginate (1%). Beads containing Trichoderma sp. spores were produced by dripping the formulations into a CaCl₂ coagulation bath. Among the formulations evaluated, formulation 3 (BNC 1%, CMC 2%, and alginate 1%) showed the best performance, with more intense growth and sporulation, as well as a significant antagonistic effect against Fusarium sp. (p = 0.004), classified as moderate antagonism. The polymeric matrix contributed to the creation of a moist and stable microenvironment, favoring the survival of the microorganism and the slow release of antifungal metabolites. These results demonstrate that encapsulation with BNC is an efficient strategy to extend the shelf life of Trichoderma sp. and reinforce the potential of this system in the formulation of more sustainable and effective bioinputs for the management of agricultural diseases.